Anterior segment parameters and intraocular pressure changes after phacoemulsification in pseudoexfoliation syndrome (Annals of Medical Research, 2021)
Aim: The aim of this study was to compare anterior segment and intraocular pressure changes in eyes with and without pseudoexfoliation after cataract surgery.Materials and Methods: This prospective study included 35 eyes of 35 patients (Group 1) without pseudoexfoliation and 40 eyes of 37 patients with pseudoexfoliation (Group 2) undergoing elective phacoemulsification surgery. The anterior segment was evaluated preoperatively and one week, and one and three months postoperatively using a Sirius-Scheimflug device. Intraocular pressures were measured using Goldman applanation tonometry. Central corneal thickness, anterior chamber volume, anterior chamber depth, anterior chamber angle, and corneal volume parameters were evaluated among the anterior segment parameters.Results: A statistically significant difference was observed between Group 1 and Group 2 in terms of pre- and postoperative anterior chamber volume, anterior chamber depth, anterior chamber angle and intraocular pressure values (p